Influences of player nationality, playing position, and height on relative age effects at women's under-17 FIFA World Cup - Romann, M.; Fuchslocher, J. (Journal of Sports Sciences, 2013)
Previous research has shown that young male soccer players who are born early in a cohort are overrepresented on elite soccer teams. Selection advantages such as this have been termed `relative age effects` (RAEs). Few studies have examined RAEs in elite women's youth soccer. Therefore, the aim of this study is to investigate the occurrence of RAEs in the Fédération Internationale de Football Association (FIFA) U-17 Women's World Cup competition and their link to playing positions. In the entire cohort of 672 players, we found significant RAEs in the geographical zones of Europe and North and Central America, no RAEs in the zones of Asia, Oceania, and South America, and significant inverse RAEs in the zone of Africa. Additionally, significant RAEs were found for goalkeepers and defenders from Europe and North and Central America. Inverse RAEs occurred for African goalkeepers, defenders, and strikers. Goalkeepers of all zones were significantly taller than players of all other playing positions. The results of this study show that remarkable RAEs do exist at elite women's youth soccer. Similar to men's soccer, there is a bias toward the inclusion of relatively older players, and a link between RAEs and playing positions.